Rural Radio in Agricultural and Rural Development - N.C.Rath; Shaik.N.Meera (Journal of Agricultural Extension Management, 2025)
Guglielmo Marconi demonstrated the communication potential of radio technology, a hundred years ago. Until Marconi ’s January 190 l transmission of the news of Queen Victoria’s death from the Isle of Wight to Cornwall , a distance of 300 kilometres, it was believed that radio waves could not follow the curvature of the earth and that broadcasts were therefore limited to a maximum of about 100 kilometres. Marconi’s experiment not only proved this wrong, but also set the stage for his first transatlantic wireless transmission, between Cornwall and Canada, in the same year